1997
DOI: 10.1046/j.1526-4610.1997.3709549.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and Sleep in Chronic Headache Sufferers: An Age‐ and Sex‐Controlled Questionnaire Study

Abstract: We studied fatigue and sleep in chronic headache sufferers in comparison to age- and sex-matched controls. We determined the prevalence and intensity of fatigue as well as several sleep features. The study was conducted in a headache center through the use of a questionnaire. One hundred thirteen headache sufferers (59 men and 54 women) and 110 controls (56 men and 54 women) were included in the analysis. Fatigue was found to be equally common in the headache sufferers (70.3%) and in the controls (60.0%). Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 3 publications
2
48
1
Order By: Relevance
“…Regarding sleep, previous studies have reported that sleeping problems were associated with TTH, although the association might be explained by a comorbid mood or anxiety disorder [2-4]. In addition, both insufficient sleep and oversleeping, as well as sleep pattern changes, have been reported as precipitating or aggravating factors of TTH in cross-sectional studies using questionnaires or interviews [5-9].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding sleep, previous studies have reported that sleeping problems were associated with TTH, although the association might be explained by a comorbid mood or anxiety disorder [2-4]. In addition, both insufficient sleep and oversleeping, as well as sleep pattern changes, have been reported as precipitating or aggravating factors of TTH in cross-sectional studies using questionnaires or interviews [5-9].…”
Section: Introductionmentioning
confidence: 99%
“…Spierings and van Hoof [46] found complaints of fatigue in 70% of headache patients, and they rated the intensity of their fatigue significantly higher than control subjects. They also found headache patients slept significantly shorter and took longer to fall asleep.…”
Section: Fatigue In Migrainementioning
confidence: 94%
“…Sleep problems in headache patients take many forms, including insomnia, sleep-related breathing disorders, circadian rhythm disorders, and parasomnias, although insomnia is the most common sleep problem. Increased rates of insomnia are found among patients who present for specialty treatment of headache [36], as well as those with chronic daily (versus episodic) headache [37], both of which characterize the population of interest here. The resulting daytime fatigue and irritability may negatively impact compliance with behavioral headache treatment.…”
Section: Sleep Disordersmentioning
confidence: 98%